Influence of Environmental Innovation on Corporate Sustainability in Latin American Companies - Araújo, Risolene Alves de Macena; Correia, Thamirys Sousa; Camara, Renata Paes de Barros (Organizações & Sociedade, 2022)
The objective of this research is to analyze the influence of environmental innovation on corporate sustainability in the main capital markets in Latin America from the perspective of the Resource-Based View. To this end, with a sample of 202 Latin American companies, data from Thomson Reuters® were collected from 2012 to 2019. The dependent variable corporate sustainability was measured by the ESG score and the explanatory variable was represented by Environmental Innovation. The estimation was performed using robust random effects regression, with panel data. The results showed that environmental innovation explains corporate sustainability when measured by the overall score of the environmental, social and corporate governance (ESG) dimensions. Nevertheless, when analyzing each dimension individually, environmental innovation is only explained by corporate governance. A possible justification is the intrinsic characteristics of governance, since it is inserted in a context focused on transparency before the market, responsibility, resource allocation, corporate sustainability, strategic management, as well as the protection of stakeholder rights. In this aspect, the findings contribute to the academic debate on the relevance of environmental innovation for sustainable development, especially for the survival of companies operating in highly competitive markets. Thus, the ability to innovate becomes an essential demand for public companies, and analyzing corporate sustainability standards and environmental innovation actions can provide valuable information about the performance of companies.